Using informatics to improve cancer surveillance. (15th September 2020) - Blumenthal, Wendy; Alimi, Temitope O; Jones, Sandra F; Jones, David E; Rogers, Joseph D; Benard, Vicki B; Richardson, Lisa C
Abstract: Objectives: This review summarizes past and current informatics activities at the Centers for Disease Control and Prevention National Program of Cancer Registries to inform readers about efforts to improve, standardize, and automate reporting to public health cancer registries. Target audience: The target audience includes cancer registry experts, informaticians, public health professionals, database specialists, computer scientists, programmers, and system developers who are interested in methods to improve public health surveillance through informatics approaches. Scope: This review provides background on central cancer registries and describes the efforts to standardize and automate reporting to these registries. Specific topics include standardized data exchange activities for physician and pathology reporting, software tools for cancer reporting, development of a natural language processing tool for processing unstructured clinical text, and future directions of cancer surveillance informatics.